ЕКСПЕРИМЕНТАЛЬНІ ДОСЛІДЖЕННЯ ЕФЕКТИВНОСТІ ЕКРАНІВ ЗУБЦЕВО-ПАЗОВОЇ КОНСТРУКЦІЇ СТАТОРІВ ТУРБОГЕНЕРАТОРІВ - Титко, О.І.; Мишастий, М.Д.; Воронін, А.І.; Хвалін, Д.І. (Інститут електродинаміки Національної академії наук України, 2017)
Shown on the basis of experiments performed at a physical model of Turbo generator that conductive screens being repeat geometry of the stator iron segments are effectively protect against of  scattering fields both the tooth zone and back stator core, and their application will significantly increase the mechanical stability of the front package. As a result of the screening in the electromagnetic field of multilayer structures the channel effect is investigated. The idea of the structure electromagnetic shielding as the most effective is substantiated. References 9, figures 15.